Reversible cognitive impairment and parkinsonism with leukoencephalopathy due to cranial dural arteriovenous fistula: Deterioro cognitivo reversible y parkinsonismo con leucoencefalopatía por fístula arteriovenosa dural craneal - Sánchez, Melanie-Lara; Dossi, Daiana E.; Ameriso, Sebastian (Journal of Applied Cognitive Neuroscience, 2022)
Parkinsonism and rapid cognitive impairment may have many causes, but only a few have specific treatment. Cranial dural arteriovenous fistula (DAVF) represents 10-15% of intracranial arteriovenous malformations. Clinical manifestations depend on location and venous drainage. It is common the presence of pulsatile tinnitus, bruits and headache or headache and papilledema. Progressive cognitive decline is an unusual presentation due to bilateral thalamic edema or cortical venous hypertension. Endovascular or surgical treatment can reverse disease symptoms. We present a 74-year old man with rapidly progressive cognitive impairment and parkinsonism and a subsequent diagnosis of dural arteriovenous fistula (DAVF). Brain MRI revealed diffuse leukoencephalopathy probably attributable to elevated venous pressure. He was treated with partial embolization with Onix and left transverse sinus angioplasty. Following the procedure, there was a substantial reduction of venous pressure signs and remarkable clinical and imaging improvement, persisting at two years follow-up. This case represents an unusual presentation of DAVF. It is important to suspect the diagnosis of DAVF in cases with rapidly evolving cognitive impairment, parkinsonism and leukoencephalopathy as it can be reversible with early treatment.